Does Information Technology Experience Matter? A Case of Secondary Schools of Kaduna State Nigeria - Harun Abubakar (University of Management and Technology, 2019)
The research was conducted using a survey research design following the guidelines of Research Advisor (2007). The study examined the school principals' perceptions about satisfaction and dissatisfaction with teacher performance regarding student development. Student development was dealt with as a comprehensive construct implying teacher efforts for academic achievement and personality development of students. The respondents comprised 300 principals of senior secondary schools in Kaduna State. Questionnaire was used as the instrument for data collection. The data collected were analyzed using simple frequencies and by calculating the mean and standard deviation. One Way Analysis of Variance (ANOVA) was applied to test the research hypotheses. All null hypotheses were rejected and research hypotheses were accepted concluding that there were significant differences between the perceptions of principals regarding teacher performance. The most interesting results were about teachers' experience; principals expressed more satisfaction with highly experienced (more than 10 years) and less experienced teachers (less than 5 years) as compared to the middle group (5-10 years). These findings initiate a serious debate about whether or not teacher experience matters. Whereas the stakeholders of secondary school education are baptized upon to guarantee that senior teachers are better performers and most eligible for leadership roles, the findings suggest that young teachers can also impress their principals by their performance and are equally eligible for leadership roles to work for holistic student development.